Epistemological Aspects Regarding the Behaviors Placed in the Leadership Logic: Array - Turtureanu, Anca; Chitu, Florentina; Cretu, Carmen Mihaela (Acta Universitatis Danubius. Œconomica, 2021)
Today's leaders not only face permanent, unpredictable and rapid changes, but are faced with a major decision, they can no longer be inspired by the way they reacted in the past, the retrospective being similar experience, to determine the direction of action, as the whole set of conditions changes rapidly. As we go through this global public health and economic crisis, companies are facing their challenges, focusing mainly on redesigning their business strategy, a task that is proving to be very difficult in these extraordinary conditions. Several companies have created dedicated teams (task force) to develop action plans strong to support the new reality, guided by numbers and statistics and lacking a very important aspect that has kept the company alive in the most difficult periods : people. Contemporary society can be characterized by a complex economic dynamic felt at all levels of human existence. In this mechanically, human creativity and the digital economy can be considered as fundamental factors underlying social progress. Regarding the methodological component of the research, in the analysis of the complex leadership phenomenon, it was focused on capturing the complexity of the phenomena, their determinants and dynamics as well as the effects of changes that occur against the deepening globalization process. The investigation procedure has been a theoretical one.